Pengaruh Partisipasi Pemakai, Pengalaman Kerja, Tingkat Pendidikan, Pelatihan dan Ketelitian terhadap Kinerja Sistem Informasi Akuntansi - Kadek Putri Minggayoni; I Putu Edy Arizona; Made Laksmi Sena Hartini (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2023)
The accounting information system is one of the providers of financial information that is much needed by parties with an interest in the company to assist in achieving the company's goals to solve a problem, make decisions and be able to produce precise and accurate information. This study aims to determine the effect of user participation, work experience, level of education, training and accuracy on the performance of accounting information systems at village credit institutions (LPD) in Ubud district. The population of this study were all LPD employees in Ubud District, totaling 382 people. Determination of the sample using purposive sampling technique, in which 78 respondents were obtained. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that the level of education, training and thoroughness has a positive effect on the performance of accounting information systems while user participation and work experience have no effect on the performance of accounting information systems.